IMPLEMENTASI PERAWATAN BERPUSAT PADA KELUARGA DI RUANG PEDIATRIC INTENSIVE CARE UNIT - Wijaya, Andra Saferi; Haryanti, Fitri; Gamayanti, Indria Laksmi (JURNAL MEDIA KESEHATAN, 2020)
ABSTRACT Child treatment in PICU is a total treatment that conducted by health workers, so the family involvement in this room is limited. Family involvement is important component in Family Centered Care. Purpose of this study is to explore The Family centered Care in PICU. This study used phenomenology qualitative and conducted with purposive sampling to 12 participants consisting of parents, nurses, physicians. Data Collected by in depth interview, observation, and study document. Study verbatim of interview was Colaizzi analyzed manually using Open Code Software. Result of themes were (1) Value of parents and child in PICU, (2) parents and nurses perception, (3) the implementation, (4) benefits, (5) challenges, (6) the expectation of Family Centered Care implementation in PICU. The restricting rules in PICU was caused family couldn’t participated for treatment child in PICU. Recommendation of this research is needed easy access for family to involve in treatment their child in PICU.